APLIKASI PENCARIAN RUTE ANGKUTAN UMUM KOTA MALANG MENGGUNAKAN MOBILE GIS DAN SMARTPHONE ANDROID: ROUTE SEARCH APPLICATION OF PUBLIC TRANSPORT IN MALANG CITY USING MOBILE GIS AND ANDROID - Dewi Rahmawati (Program Studi Teknologi Informasi, 2019)
A large population, very high mobility, congestion in every major city and the selection of public transport in carrying out daily activities are the background of making a search application for public transport routes in malang city using greedy algorithm. Inevitably, they will be troubled because of the large number of city public transportation that passes through the road. This greedy algorithm is a search algorithm that can be used to find solutions that can approach these problems, especially with the number of different public transport routes in each public transportation department. There will be many alternative roads from the place of origin to the destination. And also, the relative cost of going for each public transportation. The greedy algorithm uses a heuristic method that can calculate the estimated cost from a particular node to another node. In this discussion the reference variables include the road distance and estimated costs. This application was developed using android SDK framework, java, PHP, MySQL and Google Map. With the route search application of public transport using mobile GIS (Geographical Information System) and Android is expected to be an alternative that makes the users right in determining the public transportation that to be used both in terms of distance and time.